Implementation of a training course increased the diagnosis of histoplasmosis in Colombia (2015)
ABSTRACT : Histoplasmosis causes a significant mortality, especially persons living with human immunodeficiencyvirus/acquired immunodeficiency syndrome (HIV/AIDS) from developing countries where access to both appropriatediagnostic methods and antiretroviral therapy are limited. A total of 81 physicians assigned to 17 Colombian departments(states) received training in the clinical, epidemiological, and diagnostic aspects of histoplasmosis. Once this trainingwas received and during the period of October 2009–November 2012, these physicians sent biological samples forimmunodiagnostic, mycological, and molecular tests from their patients with suspicion of histoplasmosis. A total of1,536 samples from 768 patients were evaluated. Of the 768 patients studied, 463 (60%) were HIV positive, 214 (28%)HIV negative, and in 91 (12%) this diagnosis was unknown, and 538 (70%) were males. The 1,536 specimens studiedcomprised 722 sera, 439 blood samples, and 241 urines, which were tested by immunodiffusion (ID), culture, and anti-genuria, respectively; in addition, 134 specimens were tested by performing a molecular assay. Histoplasmosis was diag-nosed in 133 patients (17%). After the training, we observed more diagnoses from 27 to 44 cases per year. In thisstudy, a significantly increased number of histoplasmosis cases reported by year were observed after implementing aneducational training program.